2020
DOI: 10.3390/sym12081341
|View full text |Cite
|
Sign up to set email alerts
|

Computational Properties of General Indices on Random Networks

Abstract: We perform a detailed (computational) scaling study of well-known general indices (the first and second variable Zagreb indices, M1α(G) and M2α(G), and the general sum-connectivity index, χα(G)) as well as of general versions of indices of interest: the general inverse sum indeg index ISIα(G) and the general first geometric-arithmetic index GAα(G) (with α∈R). We apply these indices on two models of random networks: Erdös–Rényi (ER) random networks GER(nER,p) and random geometric (RG) graphs GRG(nRG,r). The ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Since in previous studies of RGGs (embedded in the unit square) the average degree k was shown to play a prominent role in the scaling of topological properties [25,44], before performing the scaling analysis of our random graph model, in the next section we focus on its average degree.…”
Section: Computation Of Average Measuresmentioning
confidence: 99%
See 2 more Smart Citations

Non-uniform random graphs on the plane: A scaling study

Martinez-Martinez,
Mendez-Bermudez,
Rodrigues
et al. 2021
Preprint
“…Since in previous studies of RGGs (embedded in the unit square) the average degree k was shown to play a prominent role in the scaling of topological properties [25,44], before performing the scaling analysis of our random graph model, in the next section we focus on its average degree.…”
Section: Computation Of Average Measuresmentioning
confidence: 99%
“…5, agrees with the scaling of several (normalized) topological indices with k as reported in Refs. [25,44] for Erdös-Renyi graphs and RGGs in the unit square. However, here we are providing an explicit expression for the scaling, see Eq.…”
Section: Scaling Analysis a Average Number Of Non-isolated Verticesmentioning
confidence: 99%
See 1 more Smart Citation

Non-uniform random graphs on the plane: A scaling study

Martinez-Martinez,
Mendez-Bermudez,
Rodrigues
et al. 2021
Preprint
“…This statistical approach, well known in random matrix theory studies, has been recently applied to random networks by means of topological indices, see e.g. [18][19][20]. Moreover, it has been shown that average topological indices may serve as complexity measures equivalent to standard random matrix theory measures [21,22].…”
Section: Computational Study Of Sp α (G) On Random Networkmentioning
confidence: 99%
“…Therefore, r and n give the way a RGG is generated. Very recently, RGGs have been successfully applied in nanomaterials [8]. Waxman generalized RGGs by considering a probabilistic connection function [9].…”
Section: Introductionmentioning
confidence: 99%